Noninvasive interventions in the treatment of acute destructive pancreatitis - D. Yu. Semyonov; A. A. Rebrov; V. V. Vasil'yev; N. P. Emel'yanova; O. V. Poliglotov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate potentials of various noninvasive procedures for treatment of severe acute pancreatitis.Material and methods. Treatment results of 110 patients with acute destructive pancreatitis by various noninvasive methods were analyzed. At early terms of disease the main aim of interventions was debridement and drainage of abdominal cavity and/or localized retroperitoneal fluid collections as a method of surgical detoxication at failure of conservative treatment (endovideosurgical or percutaneous puncture draining procedures were used). Revealing of the infected pancreatonecrosis, peripancreatic abscesses acted as absolute indication to their drainage which was carried out by percutaneous or lumboscopic approach. At inefficacy of noninvasive procedures traditional open interventions were carried out.Results. Of 110 patients with destructive pancreatitis treatment by noninvasive procedures was effective and sufficient in 97 cases (88,2 %).Conclusions. Adequate debridement and drainage of pathologic foci along with little surgical aggression at access in noninvasive interventions provide advantage in comparison to traditional methods.